Nocturnal delivery: First record of orchid pollinia (Orchidales: Orchidaceae) on prominent moths (Lepidoptera: Notodontidae) - Ryan A. St Laurent; María Alejandra Rodríguez; Giovanny Fagua (Revista Chilena de Entomología)
Moths are significant pollinators and flower visitors globally, however their roles and mutualistic relationships with plants remain underexplored. This study highlights the novelty of the Nystaleinae Nycterotis jacobensis (Thiaucourt, 2008) as a potential orchid pollinator, evidenced by pollinia found on its proboscis. The specimen, collected in Utría National Natural Park, Colombia, would represent the first report of a prominent moth visiting orchids in this region. Additionally, we review recent observations of Dioptinae moths feeding on flowers, suggesting their potential role as pollinators. Our findings underscore the need for further research on the biology and ecology of Neotropical moths, particularly in ecosystems vulnerable to climate change. Future studies should focus on identifying the specific orchid species visited by Nycterotis and other Nystaleinae, as well as implementing diverse methodologies to assess the impact of these nocturnal pollinators on tropical ecosystem dynamics and their response to environmental changes.